2021
DOI: 10.1123/jsep.2020-0122
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowing Against Doping Misconduct in Sport: A Reasoned Action Perspective With a Focus on Affective and Normative Processes

Abstract: Whistleblowing against doping misconduct represents an effective deterrent of doping use in elite competitive sport. The present study assessed the effects of social cognitive variables on competitive athletes’ intentions to report doping misconduct. A second objective was to assess whether the effects of social norms on whistleblowing intentions were mediated by actor prototype evaluations and group identification and orientation. In total, 1,163 competitive athletes from Greece, Russia, and the United Kingdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The finding that few athletes were aware of the reporting mechanisms available, and had concerns that their complaints would be handled improperly, merely compounds the latter quandary. Future research may wish to explore how cultural factors influence the importance athletes attribute to loyalty or fairness (see (3) and (41), for some initial findings on this topic). Given that loyalty has been suggested to be a more dominant norm within collectivist cultures than individualistic ones, large-scale quantitative studies could explore whether this is associated with the increased likelihood that athletes will overlook unethical acts (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that few athletes were aware of the reporting mechanisms available, and had concerns that their complaints would be handled improperly, merely compounds the latter quandary. Future research may wish to explore how cultural factors influence the importance athletes attribute to loyalty or fairness (see (3) and (41), for some initial findings on this topic). Given that loyalty has been suggested to be a more dominant norm within collectivist cultures than individualistic ones, large-scale quantitative studies could explore whether this is associated with the increased likelihood that athletes will overlook unethical acts (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The data reported in the present article was drawn from a larger-scale international study that investigated the psychosocial factors associated with whistleblowing against doping misconduct among competitive athletes, and the sampling methodology has been reported in detail elsewhere ( Lazuras et al, 2021 ; Barkoukis et al, 2021a ). Overall, 1,163 athletes from both individual and team sports from Greece, the Russian Federation, and the United Kingdom were recruited and their details are as follows: 480 competitive athletes (283 males, M age = 19.88, SD = 1.70) from Greece; 512 competitive athletes (341 males, M age = 20.08, SD = 5.49) from the Russian Federation; and 171 competitive athletes (121 males, M age = 20.31, SD = 1.95) from the United Kingdom.…”
Section: Methodsmentioning
confidence: 99%
“…It was demonstrated that athletes with higher levels of autonomous motivation and moral functioning, as indicated in higher scores in sportspersonship orientations (e.g., following rules, respecting officials and opponent, engaging in pro-social behaviour in sport), were also more likely to want to report witnessed or suspected doping misconduct through WBRS ( Barkoukis et al, 2021a ). Another recent study further indicated that considerations of social norms (e.g., if whistleblowing is socially approved by referent others, and if most similar others would report doping misconduct via WBRS) were also associated with intention to engage in whistleblowing among elite competitive athletes from three countries ( Lazuras et al, 2021 ). This study also indicated that, on average, athletes displayed relatively strong intention to report doping misconduct via WRBS.…”
Section: Introductionmentioning
confidence: 96%
“…In the light of alarming reports on the use of doping agents among strength sport athletes that are not subjected to anti‐doping tests, 7 the question appears warranted whether or not doping should be viewed, in some cases, from a substance‐use disorder perspective. In consideration of the acknowledged existence of a majority of athletes that strictly disapproves doping, 8,9 various different research topics were compiled and prioritized in a concerted effort including 82 anti‐doping stakeholders, 10 aiming at respecting the needs, requests, and expectations of all parties. In a variety of studies, the essential and indispensable role of conventional anti‐doping tests in combination with doping control sample long‐term storage and re‐testing programs was summarized, 11–14 highlighting the importance of harmonizing especially global anti‐doping testing frequencies, an aspect that has not been fully accomplished today 15 and which experienced a severe setback particularly during the most critical months of the COVID‐19 pandemic 16,17 .…”
Section: Introductionmentioning
confidence: 99%